A study on the properties of the 12 may wenchuan earthquake-induced debris flow - Han, Y.S.; Han, J.; Zhu, Y.Y.; Kong, Y.P.; Su, F.H.; Li, L.W.; Huang, P. (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value="{"1":2,"2":"Debris lows triggered by earthquakes are recognized globally for their huge destructive power. Studies on the development features of debris flow are essential for disaster prevention and mitigation and the results can be used as a scientific basis for assuring public security, preventing debris-flow disasters and reconstructing the af icted areas by earth-quake. Taking the, Niujuan Gully, as the case study area, this paper discusses field observations of the initiation and path of debris flows in the epicentral area of the 12 May, 2008 Wenchuan Earthquake. Based on the natural conditions and debris flow distribution in the study area, a field control network was established to monitor the gully bed, typical slopes and channel sections of different kinds of debris flows that initiated from hillslopes and gullies. We observed debris flows and their change under different rainfall circumstances, surveyed slope, section, channel and gully bed by means of GPS, GPT- 3002 total-station instrument and 3D laser scanning system and drew digital topographic maps, sectional maps and profile maps with a 1:50 scale. Based on the observed data, we probed into the erosion laws and development features(including erosion, transportation, deposition, etc) of different kinds of debris flows and analyzed debris flow discharge, erosion-deposition variation and destructive magnitude. The findings provided data support for debris flow risk assessment and monitoring systems."}" data-sheets-userformat="{"2":13057,"3":{"1":0},"11":0,"12":0,"15":"Arial","16":10}">Debris lows triggered by earthquakes are recognized globally for their huge destructive power. Studies on the development features of debris flow are essential for disaster prevention and mitigation and the results can be used as a scientific basis for assuring public security, preventing debris-flow disasters and reconstructing the af icted areas by earth-quake. Taking the, Niujuan Gully, as the case study area, this paper discusses field observations of the initiation and path of debris flows in the epicentral area of the 12 May, 2008 Wenchuan Earthquake. Based on the natural conditions and debris flow distribution in the study area, a field control network was established to monitor the gully bed, typical slopes and channel sections of different kinds of debris flows that initiated from hillslopes and gullies. We observed debris flows and their change under different rainfall circumstances, surveyed slope, section, channel and gully bed by means of GPS, GPT- 3002 total-station instrument and 3D laser scanning system and drew digital topographic maps, sectional maps and profile maps with a 1:50 scale. Based on the observed data, we probed into the erosion laws and development features(including erosion, transportation, deposition, etc) of different kinds of debris flows and analyzed debris flow discharge, erosion-deposition variation and destructive magnitude. The findings provided data support for debris flow risk assessment and monitoring systems.